Government ownership and corporate tax avoidance: empirical evidence from Malaysia - Salihu, Ibrahim Aramide; Sheikh Obid, Siti Normala; Annuar, Hairul Azlan (Pak Publishing Group, 2014)
While there have been substantial improvements in the performance of Government-linked Companies (GLCs) in Malaysia in the recent past, their tax planning activities remain a mystery. With government supports, GLCs seem to benefit more from tax avoidance practices. Given this, and in line with the call on investigating the role of government ownership in corporate tax planning by Hanlon and Heitzman (2010), this study investigates the influence of substantial government ownership on corporate tax avoidance. The data for the investigation came from the top 100 Malaysian companies based on FTSE tradable index over a three-year financial period. The results of the system GMM estimation of the dynamic panel data models using four similar measures of tax avoidance show an inconclusive finding. The relationship between government ownership and corporate tax avoidance is documented for only two of the measures. A further qualitative enquiry through personal interview sessions with ten tax auditors of IRBM was conducted to better understand the scenario. The results of the analysis of responses show a similar inconclusive finding. It was therefore concluded that Malaysian GLCs are somehow complex in tax related matters. Following this conclusion, GLCs in Malaysia need to be more transparent in tax compliance matters to restore the public confidence